Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1038/nbt831
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling reveals off-target gene regulation by RNAi

Abstract: RNA interference is thought to require near-identity between the small interfering RNA (siRNA) and its cognate mRNA. Here, we used gene expression profiling to characterize the specificity of gene silencing by siRNAs in cultured human cells. Transcript profiles revealed siRNA-specific rather than target-specific signatures, including direct silencing of nontargeted genes containing as few as eleven contiguous nucleotides of identity to the siRNA. These results demonstrate that siRNAs may cross-react with targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
1,566
8
10

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 2,081 publications
(1,642 citation statements)
references
References 8 publications
32
1,566
8
10
Order By: Relevance
“…A primary source of sequence-dependent off-target effects, at least in mammalian systems, appears to be the relatively high tolerance for mismatches between the siRNA guide strand, the ultimate targeting molecule, and the complementary target mRNA sequence, outside of the short 'core' targeting region, that is, bases 2-8, known as the guide strand's 'seed region' 3,4 . Indeed, this type of partial complementarity has been shown to underlie the mechanism of target silencing exhibited by microRNAs (miRNAs; for example, see ref.…”
Section: Specificity Of Rnai Phenotypes: Experimental Controls Lead Tmentioning
confidence: 99%
“…A primary source of sequence-dependent off-target effects, at least in mammalian systems, appears to be the relatively high tolerance for mismatches between the siRNA guide strand, the ultimate targeting molecule, and the complementary target mRNA sequence, outside of the short 'core' targeting region, that is, bases 2-8, known as the guide strand's 'seed region' 3,4 . Indeed, this type of partial complementarity has been shown to underlie the mechanism of target silencing exhibited by microRNAs (miRNAs; for example, see ref.…”
Section: Specificity Of Rnai Phenotypes: Experimental Controls Lead Tmentioning
confidence: 99%
“…However, off-target translational repression in the case of RNAi led to the observation that shorter sequences, comprising as few as 7 contiguous complementary base pairs, may be sufficient for direct RNAi-mediated silencing, which seems particularly relevant in the case of microRNA (miRNA) action. [61][62][63][64] MicroRNAs miRNAs are endogenous non-coding small RNAs (19-23 nt) found in both animal and plant genomes. [65][66][67] In plants, miRNAs seem to bind to mRNA targets by perfect or nearly perfect complementarity, and cleave the target molecules.…”
Section: Rnai Mechanism Of Actionmentioning
confidence: 99%
“…Moreover, their results suggested that the most effective siRNA overhangs have a UU or TT sequence. Since then, most of the reported siRNA sequences have been 21 bp in length (although there have also been reports of effective 23 bp [123][124][125][126][127] The action of siRNA depends on many cellular proteins; therefore, various organisms may respond to siRNA in slightly different manners. As cellular antiviral systems are intertwined with the siRNA system, the innate immune system (specifically the interferon response and the NF-kB-modulated inflammation response through Toll-like receptors) may be stimulated by siRNA.…”
Section: Rnai and Functional Genomicsmentioning
confidence: 99%
“…Thus, for clinically significant OI caused by structural defects in collagen, suppression of the Mut allele could in principle convert severe types III and IV to the minimally symptomatic OI type I, a situation particularly favorable to therapeutic strategies based on gene silencing. The promising preliminary data on stem cell transplantation in both murine models [18][19][20] and human OI 21,22 contributes to an appealing possibility for correcting the patient's own stem cells in vitro, and transplanting them back to the patient, after checking chromosomal rearrangements 23 or off-target effects 24 in vitro.…”
Section: Introductionmentioning
confidence: 99%